2017
DOI: 10.1111/bdi.12485
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profiles in euthymic patients with bipolar disorders: results from the FACE‐BD cohort

Abstract: These results confirm the existence of several distinct cognitive profiles in BD. Identification of these profiles may help to develop profile-specific cognitive remediation programs, which might improve functioning in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
6
29
0
Order By: Relevance
“…Discrete subgroups were described in this work—anchored by one “intact” and one globally impaired subgroup respectively, with a selectively impaired group intermediate. Similar findings are evident in several independent studies using the same or very similar approaches . Nearly all of the studies that have identified and characterized cognitive subgroups in BD have converged to suggest that there may be important differences between cognitive subgroups with regard to premorbid functioning, clinical course and cognitive change over time .…”
Section: Trajectory Of Cognitive Functioning In Bdsupporting
confidence: 74%
See 2 more Smart Citations
“…Discrete subgroups were described in this work—anchored by one “intact” and one globally impaired subgroup respectively, with a selectively impaired group intermediate. Similar findings are evident in several independent studies using the same or very similar approaches . Nearly all of the studies that have identified and characterized cognitive subgroups in BD have converged to suggest that there may be important differences between cognitive subgroups with regard to premorbid functioning, clinical course and cognitive change over time .…”
Section: Trajectory Of Cognitive Functioning In Bdsupporting
confidence: 74%
“…In this context, the absence of significant age differences between subgroups indicates a possible link between cognitive impairment and a more aggressive, but not necessarily more chronic, clinical course in at least some patients—which may represent a mechanism of cognitive decline. However, at least two studies with larger samples did not find any subgroup differences in the number of past mood episodes, making it unclear whether this is truly important factors for distinguishing levels of cognitive functioning in BD.…”
Section: Trajectory Of Cognitive Functioning In Bdmentioning
confidence: 98%
See 1 more Smart Citation
“…2 Among impaired individuals, several neuropsychological studies describe the presence of significant impairments, detected mainly in the domains of attention, memory and executive functions, 3 although some studies suggest a broader profile, including verbal learning and psychomotor speed impairments. 4,5 Longitudinal studies are controversial regarding the hypothesis that there is a steeper and continuous cognitive decline in BD patients in comparison to individuals with no previous history of psychiatric disorders. 6,7 Some authors have also suggested a positive correlation between cognitive functioning and functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analytic study concluded that the majority of current evidence from longitudinal studies does not appear to support a progressive nature of cognitive deficits in BD . The possible existence of several distinct cognitive profiles in BD has also been suggested …”
Section: Introductionmentioning
confidence: 99%